Low interbasin connectivity in a facultatively diadromous fish: evidence from genetics and otolith chemistry. Issue 5 (18th February 2014) - Hughes, Jane M.; Schmidt, Daniel J.; Macdonald, Jed I.; Huey, Joel A.; Crook, David A.
Abstract Southern smelts (Retropinna spp.) in coastal rivers of Australia are facultatively diadromous, with populations potentially containing individuals with diadromous or wholly freshwater life histories. The presence of diadromous individuals is expected to reduce genetic structuring between river basins due to larval dispersal via the sea. We use otolith chemistry to distinguish between diadromous and nondiadromous life histories and population genetics to examine interbasin connectivity resulting from diadromy. Otolith strontium isotope (87Sr:86Sr) transects identified three main life history patterns: amphidromy, freshwater residency and estuarine/marine residency. Despite the potential for interbasin connectivity via larval mixing in the marine environment, we found unprecedented levels of genetic structure for an amphidromous species. Strong hierarchical structure along putative taxonomic boundaries was detected, along with highly structured populations within groups using microsatellites (FST = 0.046–0.181), and mtDNA (ΦST = 0.498–0.816). The presence of strong genetic subdivision, despite the fact that many individuals reside in saline water during their early life history, appears incongruous. However, analysis of multielemental signatures in the otolith cores of diadromous fish revealed strong discrimination between river basins, suggesting that diadromous fish spend their early lives within chemically distinct estuaries rather than the more homogenous marine environment, thus avoiding dispersal and maintaining genetic structure.